2020
DOI: 10.1177/0886260520966675
|View full text |Cite
|
Sign up to set email alerts
|

A Blue Step Forward: An Exploratory Study of Law Enforcement Perceptions of Intimate Partner Violence in the Southern United States

Abstract: Intimate partner violence (IPV) is a pervasive issue that is underreported to law enforcement. One reason why individuals do not report their victimization stems from a perceived lack of support from law enforcement officials. However, law enforcement perceptions of IPV are largely unknown as the empirical literature on this topic is both limited and dated. To fill this gap in the literature, we conduct an exploratory analysis of how officers perceive IPV events. Utilizing original survey data from 498 law enf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
2
9
1
Order By: Relevance
“…Gill et al (2019) reported that most participants (92.3%) in a sample of Canadian police officers considered DFV as a serious issue and supported a strong criminal justice response. A similar finding was reported by El Sayed et al (2022) pointing toward a positive shift in attitudes among police officers. Nonetheless, it is evident that there is scope to enhance police responses and improve their attitudes.…”
Section: Contemporary Police Attitudessupporting
confidence: 88%
See 1 more Smart Citation
“…Gill et al (2019) reported that most participants (92.3%) in a sample of Canadian police officers considered DFV as a serious issue and supported a strong criminal justice response. A similar finding was reported by El Sayed et al (2022) pointing toward a positive shift in attitudes among police officers. Nonetheless, it is evident that there is scope to enhance police responses and improve their attitudes.…”
Section: Contemporary Police Attitudessupporting
confidence: 88%
“…We hypothesized that there would be a positive effect of gender and lived experience on DFV stress, attitudes, and performance. Against expectations and in contrast to McPhedran et al (2017) and El Sayed et al (2022), officers' overall attitudes toward DFV did not significantly differ by gender or lived experience. The lack of gender differences in attitudes is surprising, considering previous research has demonstrated that male police officers have less supportive attitudes toward DFV compared to their female counterparts.…”
Section: Gender and Lived Experiencecontrasting
confidence: 65%
“…Results demonstrated that when the DV incident involved a physical altercation between the victim and suspect, the odds of service referral increased by three times as compared to DV cases involving only emotional and/or psychological abuse, reiterating prior research (Kernic & Bonomi, 2007). This finding likely reflects police perceptions of urgency and severity, where physical DV is often perceived as more legitimate, credible, and serious when compared to abuse that does not produce demonstrable physical injury (Dichter et al, 2011;Eigenberg et al, 2012;El Sayed et al, 2020;Twis et al, 2018). El Sayed et al (2020), for instance, recently found that nearly 500 officers from nine Southern police agencies indicated that evidence of physical trauma was one of the most important factors influencing perceptions of victim credibility.…”
Section: Discussionmentioning
confidence: 56%
“…This finding likely reflects police perceptions of urgency and severity, where physical DV is often perceived as more legitimate, credible, and serious when compared to abuse that does not produce demonstrable physical injury (Dichter et al, 2011;Eigenberg et al, 2012;El Sayed et al, 2020;Twis et al, 2018). El Sayed et al (2020), for instance, recently found that nearly 500 officers from nine Southern police agencies indicated that evidence of physical trauma was one of the most important factors influencing perceptions of victim credibility. In the present study, it could be that officers may not have interpreted emotional and/or psychological DV as serious enough to warrant service referral.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation